An Acute Review of Talent Management in Work Place - CHAWLA, CHANCHAL; AGARWAL, MANOJ (The journal of contemporary issues in business and government, 2021)
Talent management is a continuous process that consists of retaining as well as attracting high-quality employees, augmenting their skills, and encouraging them continuously to enhance their performance. The main perseverance of talent management is to construct an enthused workforce that will stay with the corporation in the long course. Talent management assists workforces to feel involved, skilled, and encouraged, letting them put the effort into their works to achieve the corporation's business goals, which consecutively, upsurges business performance and client satisfaction. This paper reviews problem with the clarification of talent management and the deficiency of data associating various specialist statements. Later we highlight the researches which maintains a methods-oriented clarification focused on the planned talent management. In the last part, we recommend some forthcoming opportunities in associated research to advance the arena of managing talent and also associate it more thoroughly with the enormous size of activity in strategic human resources management.